Change of the topology of a superconducting thin film electromagnetically coupled with an array of ferromagnetic nanowires. (3rd December 2015) - Trezza, M; Cirillo, C; Dolgiy, A L; Redko, S V; Bondarenko, V P; Andreyenka, A V; Danilyuk, A L; Prischepa, S L; Attanasio, C
Abstract: We report on the superconducting properties of a Nb thin film deposited, with an interleaved insulating layer to avoid the proximity effect, on an array of ferromagnetic (Ni) nanowires embedded in a porous template. By investigating the T c ( H ) phase boundary and by measuring V ( I ) characteristics and critical currents as a function of the applied magnetic field, we find that the Nb film exhibits properties similar to those of a network of one-dimensional superconducting nanowires. We attribute this behavior to the stray fields of the magnetic dipoles, which create an almost regular lattice of normal regions in the superconductor, ultimately changing its topology. Furthermore, there is evidence that the magnetic pinning of vortices is negligible in this structure.